Hur påverkas hjärtfrekvens och blodlaktat av T1/T3 (tölt)finalens utformning? - Eriksson, Sangsta Elsa (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2020)
Effects of walk breaks in T1/T3 final on heart rate and lactate in Icelandic horses Icelandic horses share, with a few other breeds, the genes to perform the gaits tölt (fourbeat without suspension) and flying pace (two-beat with suspension). Characteristic for a good tölt is the clear and distinct four beat, great balance, correct topline and high but supple movements. Sport Competitions, Pace Race and Gæðinga is common competitions for Icelandic horses. T1/T3 is a Sport Competition containing three sections: 1. slow tölt; 2. slow tölt with lengthen stride distinctly on the long sides; 3. fast tölt. The five riders who receive the highest scores from the judges in the preliminary round can participate in the A-finals. In the finals the sections must be shown in both hands and the time is often increased compared to the preliminary rounds. In medium to fast speed, tölt has similar physiological responses like trot. The physiological responses in tölt seems to be higher with increasing speed and when the rider’s weight is more than 22% of the horse’s weight. The rules of walk breaks in the finals arose from riders and judge’s idea that the horses had high physiological response during the finals and therefore was a threat for the welfare of the horses. There is no public data showing the physiological responses in a T1/T3 final nor the walk breaks impact. The aim of this thesis is to examine the physiological response during a T1/T3 final and compare these results with two different finals arrangement; with walk pauses and without. The physiological response is measured by heart rate in beats/min and lactate in mmol/L blood. When horses reach 4mmol/L the anaerobic system has an important role to provide the muscles with energy compared to the aerobic system when lactate is under 4mmol/L. This study included six trained horses (age 8-19, three mares, two geldings, one stallion). Six well-educated riders rode the two final arrangements on two different days in standardized groups of three. The warmup was individual (time limit 25 min). The finals with the walk pauses was formed as follow. Section 1: slow tölt 100s, change hand 20s, slow tölt 100s. Section 2: stride lengths 110 s, change hand 20 s, walk pause 60 s, stride lengths 110s. Section 3: Fast tölt 65 s, change hand 20s, walk pause 120 s, fast tölt 65 s. The finals without walk pauses were arranged the same way but the walk pauses were excluded. Heart rate was measured and collected during rest, 10 min warmup and throughout the finals. Blood samples were collected and analyzed for lactate after section 1, 2 and 3. The results showed no significant difference on heart rate and lactate from the two final arrangements. The horses received significant higher heart rate and lactate in section fast tölt compared to slow tölt. In fast tölt the horses received heart rate 177 beats per minute (SEM= 7.9) and blood lactate concentration 3.9 mmol/L (SEM=0.7). Additionally, there was an individual range in blood lactate concentrations from 0.5-7.4 mmol/L. In conclusion, the hypothesis that there would be no difference in the physiological response in the two final arrangement is true. The hypothesis that the horses would receive over 4mmol/L blood in stride lengths and fast tölt is rejected. However, individual horses worked over 4mmol/L in fast tölt.